If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 7y + -4y + 9x = 0 Reorder the terms: X + 9x + 7y + -4y = 0 Combine like terms: 7y + -4y = 3y X + 9x + 3y = 0 Solving X + 9x + 3y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-9x' to each side of the equation. X + 9x + -9x + 3y = 0 + -9x Combine like terms: 9x + -9x = 0 X + 0 + 3y = 0 + -9x X + 3y = 0 + -9x Remove the zero: X + 3y = -9x Add '-3y' to each side of the equation. X + 3y + -3y = -9x + -3y Combine like terms: 3y + -3y = 0 X + 0 = -9x + -3y X = -9x + -3y Simplifying X = -9x + -3y
| 7m=350 | | 0.3x+0.8=1.4 | | 6p-2(5p+1)=2p+4 | | 4x+3x-9=-5+4+5x | | 1x^2-8x+14= | | 18.5=a-3.5 | | 2x-25=15 | | 2x-8=-4x+9 | | -x^2-6x+5= | | 4m+8+6m+10= | | 3(x+4)-2(x-5)=6x-2(x-5) | | 2y+7y+4y+6y= | | 96=-y+174 | | -6x+7=2x+9 | | -x^2-12x+10= | | x+57=8x+15 | | -x^2+8x+12= | | 4x+5=-6x-2 | | 3e^2x-1=6 | | 10-20/(-5)= | | -x^2-6x+10= | | 2x+4=-5x-9 | | 10x+44= | | 6(3w+5)5=-2 | | -3k(k+3)-(5+5k)=-9 | | (62x+49y)-(-35x+15y)= | | 2x-2=5x-5 | | -2(2t+10)=-36 | | 3t=6t-9 | | x+71=7x+5 | | x^2+12x+8= | | -10(s+5)=115 |